Elongation Factor Ts from the Antarctic Eubacterium Pseudoalteromonas haloplanktis TAC 125: Biochemical Characterisation, and Cloning of the Encoding Gene - RAIMO, Gennaro; LOMBARDO B.; MASULLO M.; LAMBERTI A.; LONGO O.; AND ARCARI P. (2004)
The elongation factor Ts was isolated from the psychrophilic Antarctic eubacterium Pseudoalteromonas haloplanktis TAC 125 strain (PhEF-Ts), and its functional properties were studied. At 0 °C PhEF-Ts enhanced the [3H]GDP/GDP exchange rate on the preformed PhEF-Tuâ[3H]GDP complex by 2 orders of magnitude even at very low Tu:Ts ratio, by lowering the energy of activation of the exchange reaction. PhEF-Ts is a monomeric protein, and in solution it forms a stable dimeric complex with PhEFTu. The PhEF-Ts encoding gene was cloned and sequenced. Its structural organization was similar to that of Escherichia coli because it showed at its 5¢ end the gene encoding the ribosomal protein S2. The translated amino acid sequence had a calculated molecular weight of 30762, and showed a high sequence identity with E. coli (68%) and Thermus thermophilus (44%) EF-Ts. The PhEF-Ts primary structure contains well-preserved almost all the amino acid residues interacting at the interfaces of the E. coli EF-TsâEF-Tu complex. Finally, the high concentration of PhEF-Ts in this psychrophilic eubacterium might represent an adaptive tool to ensure an efficient nucleotide exchange even at low temperature.